Labour market reforms and outcomes in Estonia - Zuzana Brixiova; Balázs Égert (Institute for the Study of Labor (IZA), 2012)
The unemployment rate in Estonia rose sharply in 2010 to one of the highest levels in the EU, after the country entered a severe recession in 2008. While the rate declined relatively rapidly in 2011, it remained high especially for the less educated. In 2009, the Employment Contract Law relaxed employment protection legislation and sought to raise income protection of the unemployed to facilitate transition from less to more productive jobs while mitigating social costs. Utilizing a search model, this paper shows that increasing further labour market flexibility through reducing the tax wedge on labour would facilitate the structural transformation and reduce the long-term unemployment rate. Linking increases in unemployment benefits to participation in job search or training programmes would improve the unemployed workers' incentives to search for jobs or retrain and the medium term labour market outcomes. Social protection schemes for the unemployed should be also strengthened as initially intended to give the unemployed sufficient time to search for adequate jobs or retrain for new opportunities.
urn:nbn:de:101:1-201205026019
Keywords: J08; J64; E24; 330; labour market reforms; search model; Estonia; OECD countries; Arbeitslosigkeit; Arbeitsmarktflexibilität; Arbeitslosenversicherung; Arbeitsuche; Umschulung